RELATIONSHIP BETWEEN DAY OF COLLECTION AND EMBRYO RECOVERY IN SUPEROVULATED ALPACAS - Cervantes F., Miriam (2011)
The relationship between day of collection and embryo recovery was studied inmultiparous adult alpacas. Females with ?7 mm follicles were superovulated, mated withfertile males (day 0 = day of service) and embryos were recovered on day 5 (G1), 6 (G2) and 7 (G3) post copula, where the number and size of corpora lutea were echographicallyevaluated. In Exp. 1, 14 females were slaughtered and embryos were recovered from theuterine horns and the oviduct. In Exp. 2, embryos were recovered in vivo from 21 females.Each uterine horn was flushed with 250 ml of PBS using a Foley catheter; and oviductswere flushed from the utero-tubal junction to the fimbria using 20 ml of PBS. The numberand rate of embryos recovered from the uterine horns was higher in G2 and G3 as comparedto G1 (p<0.05), while in the oviduct was higher in G1. Collected embryos from uterinehorns had the condition of excellent and good in 81.4% (35/43) in Exp. 1 and 74.5% (38/51)in Exp. 2, and without statistical differences between treatments in each experiment. Themost frequent level of embryo development was hatching blastocyst (77.7%, 73/94), andwithout differences between G2 and G3. It was concluded that embryos could be recovereduntil day 5 after mating in oviducts and from day 6 onwards in the uterine horns.